2018
DOI: 10.1177/1359105318792080
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in patients with obstructive sleep apnoea: The role of hostility and coping self-efficacy

Abstract: We aimed to assess whether hostility and coping self-efficacy are associated with psychological distress in obstructive sleep apnoea patients. Furthermore, we examined whether coping self-efficacy mediates the association between hostility and psychological distress. We included 150 obstructive sleep apnoea patients (Apnoea-Hypopnoea Index ⩾5; 68% male; mean age: 48.9 ± 9.5 years). Regression models showed that hostility and poor coping self-efficacy were strongly associated with psychological distress in obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 80 publications
0
8
1
Order By: Relevance
“…Interestingly, whereas in other samples of persons with chronic conditions 27,28 reporting lower levels of illness-related emotional representations (eg, anger or anxiety related to disease) have been associated with better self-efficacy, our findings showed that the participants with more negative feelings about T2DM tended to have higher self-efficacy for managing T2DM. Our sample endorsed higher scores on emotional representations compared with other T2DM samples, 15,29 which may be partially driving our findings.…”
Section: Discussioncontrasting
confidence: 84%
“…Interestingly, whereas in other samples of persons with chronic conditions 27,28 reporting lower levels of illness-related emotional representations (eg, anger or anxiety related to disease) have been associated with better self-efficacy, our findings showed that the participants with more negative feelings about T2DM tended to have higher self-efficacy for managing T2DM. Our sample endorsed higher scores on emotional representations compared with other T2DM samples, 15,29 which may be partially driving our findings.…”
Section: Discussioncontrasting
confidence: 84%
“…CSE comprises personal beliefs concerning mastery of three coping skills: (1) stopping negative emotions and thoughts, (2) problem-focused coping, and (3) obtaining social support. CSE domains have been widely applied to patient-relevant contexts, such as explaining the relationships between hostility and mental health (Timkova et al, 2018), cyber victimization and internalizing mental illness (Trompeter, Bussey, & Fitzpatrick, 2018), and child abuse and ADHD (Singer, Humphreys, & Lee, 2016). Within an Emotional Labor framework, CSE may manifest as a mitigating factor of the stresses faced in difficult interpersonal work.…”
Section: Coping Among Staff Working With High-risk Patientsmentioning
confidence: 99%
“…Therefore, it is paramount to consider the significant psychological factors associated with OSA (Gałecki et al, 2011). Timkova et al (2020) state that apart from the physical symptoms that patients with OSA experience, they also suffer from psychological distress and according to previous research, various psychiatric disorders are also prominent in this population (Guglielmi et al, 2018;Shoib et al, 2022). However, these psychiatric illnesses could be triggered by OSA's biological and/or psychosocial effects (Pochat et al, 1993).…”
Section: Obstructive Sleep Apnea and Psychological Distressmentioning
confidence: 89%